1977
DOI: 10.1136/adc.52.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal bacterial flora in early stages of transient monosaccharide intolerance in infants.

Abstract: SUMMARY The aerobic and anaerobic bacterial flora of the duodenum were studied in 10 infants with transient monosaccharide intolerance. 5 infants had protracted diarrhoea after an episode of acute gastroenteritis and 5 had acute gastroenteritis. The duration of monosaccharide intolerance ranged from 1 to 20 days. Serial intubations were performed on 8 infants. In 5 of 8 cases the bacterial flora were of a normal type at the first intubation at 0-4 days after the onset of monosaccharide intolerance. In 4 of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…most often E. coli, Kleb siella pneumoniae , and Ent erobacter sp. (27)(28)(29)(30)(32)(33)(34)(35)(36). Similar changes have been found in adults with acute infectious diarrhea (37,38).…”
Section: Jejunal Bacterial Overgrowth In Acute and Persistent Infecti...supporting
confidence: 75%
See 1 more Smart Citation
“…most often E. coli, Kleb siella pneumoniae , and Ent erobacter sp. (27)(28)(29)(30)(32)(33)(34)(35)(36). Similar changes have been found in adults with acute infectious diarrhea (37,38).…”
Section: Jejunal Bacterial Overgrowth In Acute and Persistent Infecti...supporting
confidence: 75%
“…by unknown mechanisms , monosaccharide transport in experimental animals (47,48), but whether such occurs in humans is difficult to prove. Gracey et al (22) found unconjugated bile salts in the small bowel of children with bacterial overgrowth and suggest that this might be causally related to monosaccharide malabsorption in these children ; however, Kilby et al (36) failed to find bacteria capable of deconjugating bile salts within the sma ll bowel of children at the time of onset of their monosaccharide malabsorption. In those instances in which EPEe se ro t y pe s have been identified among the jejunal flora (26,28), no information has been obtained on whether these strains are enteroadherent (49), a property that can be associated with prolonged diarrhea (50,51), except in one case where such bacteria were identified (7).…”
Section: Jejunal Bacterial Overgrowth In Acute and Persistent Infecti...mentioning
confidence: 99%
“…Monosaccharide intolerance occurs in less than 20% of infants with protracted diarrhea and is positively correlated with the loss of intestinal surface area (25). It has been reported in association with a high percentage of pathogenic organisms on duodenal fluid culture (26), as well as with bacterial overgrowth of nonpathogens in infants with protracted diarrhea (27). Glucose transport mechanisms remained unaffected by enterotoxin-producing bacterial pathogens (28), but the effect of EPEC on glucose transport has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of carbohydrate metabolism in babies is sometimes necessary because babies who cannot metabolize carbohydrates can develop diarrhea and become dehydrated. Currently, determinations are carried out by administering infant formulas containing different sugars to see which causes the intolerance (16,18). A noninvasive method of assessing the intolerance would be faster, more costeffective, and less stressful to the sick infant.…”
mentioning
confidence: 99%